2018
DOI: 10.1590/1414-431x20176799
|View full text |Cite
|
Sign up to set email alerts
|

Agonistic activity of tamoxifen, a selective estrogen-receptor modulator (SERM), on arthritic ovariectomized mice

Abstract: Arthritis is positively associated with the decline of sex hormones, especially estrogen. Tamoxifen (TMX) is a selective estrogen receptor modulator, possessing agonist or antagonistic activity in different tissues. Thus, the objective of this study was to investigate the effect of TMX on the zymosan-induced arthritis model. Female Swiss normal and ovariectomized (OVX) mice were divided into groups and treated for five days with TMX (0.3, 0.9 or 2.7 mg/kg) or 17-β-estradiol (E2, 50 µg/kg). On the fifth day, ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Whilst functional significance of estrogen-induced down-regulation of blood neutrophils is yet to be elucidated, the study highlights the potential of estrogenic compounds in modulating neutrophil biology in cancer patients. Tamoxifen, a widely used drug in ERα-positive breast cancer, is reported to function as a selective estrogen receptor agonist in neutrophils and hematopoietic progenitor cells [ 36 , 37 ]. There have been reports of tamoxifen-induced neutropenia in breast cancer patients [ 38 , 39 ], which may be caused by tamoxifen’s estrogenic activity in neutrophils.…”
Section: Discussionmentioning
confidence: 99%
“…Whilst functional significance of estrogen-induced down-regulation of blood neutrophils is yet to be elucidated, the study highlights the potential of estrogenic compounds in modulating neutrophil biology in cancer patients. Tamoxifen, a widely used drug in ERα-positive breast cancer, is reported to function as a selective estrogen receptor agonist in neutrophils and hematopoietic progenitor cells [ 36 , 37 ]. There have been reports of tamoxifen-induced neutropenia in breast cancer patients [ 38 , 39 ], which may be caused by tamoxifen’s estrogenic activity in neutrophils.…”
Section: Discussionmentioning
confidence: 99%
“…Whilst functional signi cance of estrogen-induced down-regulation of blood neutrophils is yet to be elucidated, the study highlights the potential of estrogenic compounds in modulating neutrophil biology in cancer patients. Tamoxifen, a widely used drug in ERα-positive breast cancer, is reported to function as a selective estrogen receptor agonist in neutrophils and hematopoietic progenitor cells [36,37]. There have been reports of tamoxifen-induced neutropenia in breast cancer patients [38,39], which may be caused by tamoxifen's estrogenic activity in neutrophils.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that hormones such as progesterone [18,19] and estradiol [10,[20][21][22] produce anti-inflammatory effects in several models of arthritis [23], but their modulatory properties are still contradictory. Our present results show that ovariectomy increase the articular inflammation in zymosan-induced arthritis.…”
Section: Discussionmentioning
confidence: 99%